Climates, landscapes, and civilizations - Giosan, Liviu (Geophysical monograph, 2012)
Published by the American Geophysical Union as part of the Geophysical Monograph Series. Climates, Landscapes, and Civilizations brings together a collection of studies on the history of complex interrelationships between humans and their environment by integrating Earth science with archeology and anthropology. At a time when climate change, overpopulation, and scarcity of resources are increasingly affecting our ways of life, the lessons of the past provide multiple reference frames that are valuable for informing our future decisions and action plans. Volume highlights i.